Off the Map? Locating the Emerging Church: A Comparative Case Study of Congregations in the Pacific Northwest - Wollschleger, Jason (Review of religious research, 2012)
This article seeks to clear up the conceptual confusion around the identity and practices of congregations labeled as Emerging. This research is motivated in part by Chaves (J Sci Study Relig 49(1):1–14, 2010) recent diagnosis of the social scientific study of religion literature as suffering from a religious congruence fallacy in which behavior is assumed to follow one’s religious label; rather than assume similarity as a result of the Emerging label this article seeks to uncover the distinctive practices of congregations labeled as Emerging and to offer a comparative analysis. Additionally, this article fills a gap in the social scientific literature by providing description of the actual practices and worship of Emerging congregations from a multi-site, congregational field research project in the Pacific Northwest. Drawing on participant observation, pastor interviews, focus groups, and paper/web resources this paper clarifies what is meant by the term the emerging church. It is shown that the emerging church in Seattle is comprised of a spectrum of congregations that are adept at attracting young adults. Despite their apparent similarities, the congregations on the ends of this spectrum are shown to belong to distinct subcultures. These are then compared to the existing dominant, Protestant subcultures in the Pacific Northwest.